Cervical Spinal Fusion in Adult Patients With Rheumatoid Arthritis: A National Analysis of Complications and 90-day Readmissions. Issue 1 (1st January 2021) - Fields, Michael W.; Lee, Nathan J.; Hong, Daniel Y.; Para, Ashok; Boddapati, Venkat; Mathew, Justin; Kim, Jun S.; Lombardi, Joseph; Lehman, Ronald A.; Riew, K. Daniel
Abstract : Study Design: Retrospective cohort study. Objective: The purpose of this study was to utilize the National Readmission Database to determine the national estimates of complication and 90-day readmission rates associated with cervical spinal fusion in adult patients with rheumatoid arthritis (RA). Summary of Background: RA patients who undergo cervical spine surgery are known to be at high risk for readmissions, which are costly and may not be reimbursed by Medicare. Methods: The National Readmission Database was queried for adults (>18 years) diagnosed with RA undergoing cervical spine fusion. Patient, operative, and hospital factors were assessed in bivariate analyses. Independent risk factors for readmissions were identified using stepwise multivariate logistic regression. Results: From 2013 to 2014, a total of 5597 RA patients (average age: 61.5 ± 11.2 years, 70.9% female) underwent cervical spine fusion. A total of 691 (12.3%) patients were readmitted within 90 days (Table 1 ). Index inpatient complications included dysphagia (readmitted: 7.9% vs. non-readmitted: 5.1%; P = 0.003), urinary tract infection (UTI) (8.8% vs. 3.7%; P < 0.001), respiratory-related complications (7.6% vs. 3.4%; P < 0.001), and implant-related complications (5.4% vs. 2.7%; P < 0.001). Multivariate logistic regression demonstrated the following as the strongest independent predictors for 90-day readmission: intraoperative bleeding (odds ratio [OR]: 3.6, P = 0.001), inpatient Deep Vein Thrombosis (DVT) (OR 4.1, P = 0.004), and patient discharge against medical advice (OR 33.5, P = 0.001). Conclusion: Readmission rates for RA patients undergoing cervical spine surgery are high and most often due to postoperative infection (septicemia, UTI, pneumonia, wound). Potential modifiable factors which may improve outcomes include minimizing intraoperative blood loses, postoperative DVT prophylaxis, and discharge disposition. Level of Evidence: 3 Abstract : Many patients with rheumatoid arthritis (RA) require surgical intervention for refractory or severe cases of cervical disease. The purpose of this study was to utilize the National Readmission Database to determine the national estimates of complication and 90-day readmissions associated with spinal fusion in adult patients with RA.